Dispositional Mindfulness and Post-traumatic Stress Symptoms in Emergency Nurses: Multiple Mediating Roles of Coping Styles and Emotional Exhaustion - Yuan, Yuan; Wang, Zonghua; Shao, Yanxia; Xu, Xia; Lu, Fang; Xie, Fei; Sun, Wei (Frontiers in Psychology, 2022)
Objective: To explore the relationships between dispositional mindfulness and their post-traumatic stress symptoms (PTSS) of emergency nurses, and the mediating effects of coping styles and emotional exhaustion. Methods: A cross-sectional survey study was conducted to collect data on dispositional mindfulness, coping styles, emotional exhaustion, and PTSS among 571emergency nurses from 20 hospitals in Chongqing, China. Correlation and structural equation mod-els (SEMs) were used to evaluate the relationship among variables. Results: Emergency nurses with lower dispositional mindfulness, higher emotional exhaustion and preference for negative coping revealed more PTSS. The effect of negative coping on PTSS was partially mediated by emotional exhaustion. Negative coping and emotional exhaustion played concurrent and sequential mediating roles between dispositional mindfulness and PTSS. Conclusion: This study has made a significant contribution to existing literature. It was suggested to develop interventions aimed at enhancing mindfulness, reducing negative coping strategies, and alleviating emotional exhaustion, which may be effective at reducing or alleviating post-traumatic stress symptoms of emergency nurses.